Monocyte Subsets Have Distinct Patterns of Tetraspanin Expression and Different Capacities to Form Multinucleate Giant Cells - Champion, Thomas C.; Partridge, Lynda J.; Ong, Siew-Min; Malleret, Benoit; Wong, Siew-Cheng; Monk, Peter N. (Frontiers in Immunology, 2018)
Monocytes are able to undergo homotypic fusion to produce different types of multinucleated giant cells, such as Langhans giant cells in response to M. tuberculosis infection, or foreign body giant cells in response to implanted biomaterials. Monocyte fusion is highly coordinated and complex, with various soluble, intracellular and cell surface components mediating different stages of the process. Tetraspanins such as CD9, CD63 and CD81 are known to be involved in cell:cell fusion and have been suggested to play a role in regulating homotypic monocyte fusion. However, peripheral human monocytes are not homogenous: they exist as a heterogeneous population consisting of three subsets, classical (CD14++CD16-), intermediate (CD14++CD16+) and nonclassical (CD14+CD16+) at steady state. During infection with mycobacteria, the circulating populations of intermediate and nonclassical monocytes increase, suggesting they may play a role in the disease outcome. Human monocytes were separated into subsets and then induced to fuse using concanavalin A. The intermediate monocytes were able to fuse faster and form significantly larger giant cells than the other subsets. When antibodies targeting tetraspanins were added, the intermediate monocytes responded to anti-CD63 by forming smaller giant cells, suggesting an involvement of tetraspanins in fusion for at least this subset. However, the expression of fusion-associated tetraspanins on monocyte subsets did not correlate with the extent of fusion or with the inhibition by tetraspanin antibody. We also identified a CD9High and a CD9Low monocyte population within the classical subset. The CD9High classical monocytes expressed higher levels of tetraspanin CD151 compared to CD9Low classical monocytes but the CD9High classical subset did not exhibit greater potential to fuse and the role of these cells in immunity remains unknown. With the exception of Dendrocyte-Expressed Seven Transmembrane Protein (DC-STAMP), which was expressed at higher levels on the intermediate monocyte subset, the expression of fusion-related proteins between the subsets did not clearly correlate with their ability to fuse. We also did not observe any clear correlation between giant cell formation and the expression of pro-inflammatory or fusogenic cytokines. Although tetraspanin expression appears to be important for the fusion of intermediate monocytes, the control of multinucleate giant cell formation remains obscure.